Comparative carcinogenicity for mouse-skin of smoke condensates prepared from cigarettes made from the same tobacco cured by two processes. - Roe, F; Clack, J; Bishop, D; Peto, R (1970)
Bright tobacco grown in Mexico was either flue-cured and redried (FC) or air-cured and bulk-fermented (AC). Both FC and AC were made into cigarettes standardized for draw resistance. FC and AC cigarettes were smoked under similar conditions in a smoking machine (one 2-second 25 ml. puff per minute down to a 20 mm. butt length). Condensates were kept at 0-4° C. until applied to the skin of mice.Three groups of 400 female Swiss mice were treated as follows: Group 1- thrice weekly application of 60 mg. FC in 0.25 ml. acetone to the clipped dorsal skin: Group 2- similar treatment with AC; Group 3-thrice weekly application of 0.25 ml. acetone only.Chemical analysis of the 2 tobaccos and 2 condensates revealed only small differences in composition and it is noteworthy that the concentration of reducing sugars was almost as high as in the AC tobacco as in the FC tobacco.The risk of development of skin tumours, particularly malignant skin tumours, was higher in FC-treated mice than in AC-treated mice (p < 0.01), but the difference may have been due to the use of equal weights of condensates rather than the use of extracts from equal numbers of cigarettes, since the AC cigarettes produced more condensate. The rates of detection of pulmonary tumours also varied between groups (p < 0.01) but this does not necessarily imply that the incidence rates of pulmonary tumours varied. There was no evidence that the detection or incidence rates of any other neoplasms, including malignant lymphoma, were affected by treatment with either of the condensates.